Renewable sources of energy in farming - Babula, Mateusz (Journal of Education, Health and Sport, 2018)
One of significant elements of balanced progress, bringing in considerable ecological and energetic effects, is making use of energy from renewable sources. The development and exploitation of renewable energy is the proper course of action in favour of respecting the energy from conventional sources, as well as increase in energetic efficiency. Farming, aside from its basic function of producing food, may also provide materials for producing electrical and thermal energy, as well as fuel. Such materials may not only be farming products, but also its by-products or waste. By using them to produce energy or fuel, we gain doubled profit – we reduce the problem of management of these products and the following environmental burden and we diminish the consumption of conventional sources.